Therapeutic Potential of Stem Cell-Derived Extracellular Vesicles on Atherosclerosis-Induced Vascular Dysfunction and Its Key Molecular Players - Comariţa, Ioana Karla; Vîlcu, Alexandra; Constantin, Alina; Procopciuc, Anastasia; Safciuc, Florentina; Alexandru, Nicoleta; Dragan, Emanuel; Nemecz, Miruna; Filippi, Alexandru; Chiţoiu, Leona; Gherghiceanu, Mihaela; Georgescu, Adriana (Frontiers in Cell and Developmental Biology, 2022)
Atherosclerosis is a progressive, chronic inflammatory disease of the large arteries caused by the constant accumulation of cholesterol, followed by endothelial dysfunction and vascular inflammation. We hypothesised that delivery of extracellular vesicles (EVs), recognized for their potential as therapeutic targets and tools, could restore vascular function in atherosclerosis. Herein, we explored by comparison the potential beneficial effects of EVs from subcutaneous adipose tissue stem cells (EVs (ADSCs)) or bone marrow mesenchymal stem cells (EVs (MSCs)) on the consequences of atherogenic diet on vascular health. Also, the influences of siRNA targeting Smad2/3 (Smad2/3siRNA) on endothelial dysfunction and its key molecular players were analyzed. For this study, animal model of atherosclerosis (HH) was transplanted with EVs (ADSCs) or EVs (MSCs) transfected or not with Smad2/3siRNA. For controls, healthy or HH animals were used. The results indicated that, by comparison with the HH group, the treatment with EVs(ADSCs) or EVs(MSCs) alone or in combination with Smad2/3siRNA of HH animals induced a significant decrease in the main plasma parameters and a noticeable improvement in the structure and function of the thoracic aorta and carotid artery along with a decrease in the selected molecular and cellular targets mediating their changes in atherosclerosis: (1) a decrease of expression of structural and inflammatory markers COL1A1, α-SMA, Cx43, VCAM-1, MMP-2; (2) a slight infiltration of total/M1 macrophages and T-cells; (3) a reduced level of cytosolic ROS production; (4) a significant diminution in plasma concentrations of TGF-β1 and Ang II proteins; (5) significant structural and functional improvements (thinning of the arterial wall, increase of the inner diameter, enhanced distensibility, diminished VTI and Vel, and augmented contractile and relaxation responses); (6) a reduced protein expression profile of Smad2/3, ATF-2, NF-kBp50/p65 and a significant decrease in the expression levels of miR-21, miR-29a, miR-192, miR-200b, miR-210 and miR-146a. We can conclude that: (1) stem cell-derived EV therapies, especially the EVs (ADSCs) led to regression of structural and functional changes in vascular wall and of key orchestrator expression in the atherosclerosis-induced endothelial dysfunction; (2) transfection of EVs with Smad2/3siRNA amplified the ability of EVs(ADSCs) or EVs(MSCs) to regress the inflammation-mediated atherosclerotic process.